Activity ranking of synthetic analogs targeting vascular endothelial growth factor receptor 2 by an integrated cell membrane chromatography system. Issue 24 (24th November 2015) - Wang, Dongyao; Lv, Diya; Chen, Xiaofei; Liu, Yue; Ding, Xuan; Jia, Dan; Chen, Langdong; Zhu, Zhenyu; Cao, Yan; Chai, Yifeng
Abstract : Evaluating the biological activities of small molecules represents an important part of the drug discovery process. Cell membrane chromatography (CMC) is a well‐developed biological chromatographic technique. In this study, we have developed combined SMMC‐7721/CMC and HepG2/CMC with high‐performance liquid chromatography and time‐of‐flight mass spectrometry to establish an integrated screening platform. These systems was subsequently validated and used for evaluating the activity of quinazoline compounds, which were designed and synthesized to target vascular endothelial growth factor receptor 2. The inhibitory activities of these compounds towards this receptor were also tested using a classical caliper mobility shift assay. The results revealed a significant correlation between these two methods ( R 2 = 0.9565 or 0.9420) for evaluating the activities of these compounds. Compared with traditional methods of evaluating the activities analogous compounds, this integrated cell membrane chromatography screening system took less time and was more cost effective, indicating that it could be used as a practical method in drug discovery.